DRUG SALES INFORMATION SYSTEM AT FLORA FARMA PHARMACY WEB-BASED - Wendra Jumaisarki; Devi Krisber (INFOKUM, 2020)
Apotek Flora Farma is a pharmacy that is engaged in drug sales. Currently, the system that is currently running at the Flora Farma pharmacy is still using a manual system so that it often experiences difficulties in making reports and calculations. The researcher aims to analyze the current system. After knowing the drawbacks and problems that exist in the Flora Farma pharmacy, the author designs a more effective system that can be implemented using a MYSQL database and using PHP language to build a web-based sales information system. The final result of this research, the researcher aims to create a sales information system to handle sales data input and then process it to produce output in the form of cashier reports, purchase reports, and sales reports.